The Effect Of Color Variation And Water Appplication On The Effectiveness Of Fruit Flies Traps In Mango Orchards (Mangifera Indica L.) - Muhammad Fais Andriansyah; Wiharyanti Nur Lailiyah; Suhaili ‎; Adiet Cantyo Pamungkas (UNIVED Press, Dehasen University Bengkulu, 2025)
The Purpose: The primary objective of this study is to assess the impact of trap color variation and the presence of water media on enhancing the effectiveness of fruit fly (Bactrocera spp.) capture in the mango orchard (Mangifera indica L.) owned by PT Galasari Gunung Sejahtera. Methodology: The research method employed a factorial Randomized Complete Block Design (RCBD) with two main factors, namely trap color (red, yellow, brown, orange) and the presence of water media (with or without water). Eight treatment combinations were generated, each repeated four times. The parameters analyzed included the number of fruit flies captured during the first and second weeks after the traps were installed. Results: Traps equipped with water media were found to capture significantly more fruit flies compared to traps without water media, in both the first and second weeks. Meanwhile, variations in trap color did not show a significant effect on the number of fruit flies captured. Findings: The presence of water media enhanced the attractiveness of the traps to fruit flies, while trap color was not a major factor in attracting them. Novelty: This study highlights the importance of adding water media to traps as a simple yet effective innovation for controlling fruit flies in mango orchards. Originality: The research provides the latest empirical data on the combined use of water and trap color under real field conditions, an area that remains limited in the local research literature. Conclusion: Traps containing water media are recommended as an effective method to control fruit fly populations in mango orchards, without relying on trap color variations. Article Type: Empirical Research Article.